(untitled) - Lee, S. T. (Boca Raton, 2004)
The first in a new series on polymeric foams, Polymeric Foams: Mechanisms and Materials provides the basics of foaming, addressing scientific principles and engineering parameters alongside their fundamental material characteristics and shared mechanisms of both thermoplastic and thermoset polyurethane foams, which are traditionally approached separately in the industry. Both lightweight and strong, plastic foams continue to gain popularity across a wide range of industries as cleaner alternatives are implemented throughout the foaming process. This book offers a convenient and straightforward foundation to engineers and researchers in the foam industry as well as those in other industries that benefit from polymeric foams. Well-organized chapters written by an international collection of well-known practitioners and academics compile previously scattered information on polymeric foaming mechanisms, corresponding chemistry and physics, resin and blowing agents, and the latest advances in foams research. It also includes 140 contextual Illustrations, 35 tables, and more than 700 references all arranged as a quick study of fundamentals and as a resource for further research. Polymeric Foams: Mechanisms and Materials offers insight for a better understanding of foaming that will encourage innovations that improve safety and cost-efficiency while reducing energy consumption, waste and environmental impact.
Keywords: Plastic foams